New-Onset Systemic Lupus Erythematosus after mRNA SARS-CoV-2 Vaccination - Báez-Negrón, Laisha; Vilá, Luis M. (Case Reports in Rheumatology, 2022)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease resulting from the interaction of genetic and environmental factors. In addition, some antiviral vaccines have been associated with the onset of SLE. Few cases of SLE occurring after SARS-CoV-2 mRNA have been reported. Herein, we report the case of a 27-year-old woman with type I diabetes mellitus and family history of SLE who presented with symmetric inflammatory polyarthritis of the proximal interphalangeal joints, metacarpophalangeal joints, wrists, knees, and ankles two weeks after receiving the second dose of the SARS-CoV-2 mRNA-1273 vaccine. Laboratory results revealed positive antinuclear, anti-dsDNA, anti-Ro, and anti-La/SSB antibodies and low C4 levels. She was initially treated with low-dose prednisone and hydroxychloroquine. Hydroxychloroquine was discontinued after she developed an urticarial rash. Subsequently, mycophenolate mofetil was added after she developed proteinuria. This case highlights the importance of considering the diagnosis of SLE in patients who present with inflammatory polyarthritis after COVID-19 vaccination.